Alive or Undead? Biopolitics between Esposito's Vitalism and Lacanian Psychoanalysis. Issue 1 (March 2016) - Nedoh, Boštjan
Abstract : This article tries to establish a possible dialogue between the way in which two influential contemporary theories, Roberto Esposito's biopolitical theory and Jacques Lacan's psychoanalysis, approach racism and the constitution of Otherness. After summing up key concepts in Esposito's theory, the article lays out the very deadlock in his work, represented by his assumption of racial difference or Otherness as inscribed in the bio-logical content of human life. However, by interpreting Jewishness under Nazism in terms of 'undead' 'flesh without body', Esposito himself crosses paths with the psychoanalytic approach, in so far as Lacan defined the Freudian death drive using the same term. The second part of the article is thus dedicated to the articulation of the relations between primal repression, trauma and jouissance, out of which can be derived an alternative conception of biopolitics, based on the discursive constitution of Otherness, rather than on the assumption that it is a biological fact.